Development of a Scaffolding-Based E-Module Integrated with Educational Games on Market Equilibrium Material to Enhance the Problem-Solving Skills of Grade X Students at SMA Negeri 1 Kelapa, West Bangka - Widyaningsih Sinaga, Artika Meilinda; Rosidah, Rosidah (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study aims to develop, validate, and test the effectiveness of a scaffolding-based e-module integrated with educational games on the topic of market equilibrium to improve students’ problem-solving skills in economics learning. The research utilized the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. A total of 72 students from SMA Negeri 1 Kelapa participated in the study, divided into experimental and control groups. Data were collected through validation questionnaires, pre-tests, and post-tests. The results showed that the e-module obtained a very high level of feasibility, with average validation scores of 3.86 from material experts, 3.88 from media experts, 3.95 from teachers, and 3.49 from students, indicating that the product met the quality criteria for instructional media. Furthermore, effectiveness testing revealed that students in the experimental class achieved an N-Gain score of 0.56, categorized as moderate, which was significantly higher than the control class score of 0.30. These results suggest that the scaffolding-based e-module integrated with educational games is both feasible and effective in enhancing students’ problem-solving skills and learning engagement in economics education.